Casein and soybean protein-based thermoplastics and composites as alternative biodegradable polymers for biomedical applications - Vaz, C. M. (2003)
This work reports on the development and characterization of novel meltable polymers and composites based on casein and soybean proteins. The effects of inert (Al(2)O(3)) and bioactive (tricalcium phosphate) ceramic reinforcements over the mechanical performance, water absorption, and ioactivity behavior of the injection-molded thermoplastics were examined. It was possible to obtain materials and composites with a range of mechanical properties, which might allow for their application in the biomedical field. The incorporation of tricalcium phosphate into the soybean thermoplastic decreased its mechanical properties but lead to the nucleation of a bioactive calcium-phosphate film on their surface when immersed in a simulated body fluid solution. When compounded with 1% of a zirconate coupling agent, the nucleation and growth of the bioactive films on the surface of the referred to composites was accelerated. The materials degradation was studied for ageing periods up to 60 days in an isotonic saline solution. Both water uptake and weight loss were monitored as a function of the immersion time. After 1 month of immersion, the materials showed signal of chemical degradation, presenting weight losses up to 30%. However, further improvement on the mechanical performance and the enhancement of the hydrolytic stability of those materials will be highly necessary for applications in the biomedical field